2009
DOI: 10.1590/s0103-90162009000200011
|View full text |Cite
|
Sign up to set email alerts
|

Citrus sinensis leaf petiole and blade colonization by Xylella fastidiosa: details of xylem vessel occlusion

Abstract: Citrus variegated chlorosis (CVC), caused by Xylella fastidiosa, is an important disease of citrus in Brazil. X. fastidiosa is restricted to xylem vessels of plants and knowledge regarding xylem colonization is still limited. Our goal was to verify how this bacterium colonizes and spreads within xylem vessels of sweet orange Citrus sinensis cv. Pêra. Petioles and pieces of leaf blades from naturally infected plant exhibiting characteristic symptoms were prepared for light microscopy (LM), scanning electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 22 publications
2
22
0
1
Order By: Relevance
“…Alves et al . () also verified that in citrus petioles, the predominant secondary cell wall deposition is the pitted type instead of the helical type predominant in grape (Fritschi et al ., ), which reinforces the hypothesis that the slower X. fastidiosa colonization in citrus compared to grape might be related to morphological differences in the xylem between these species.…”
Section: Discussionmentioning
confidence: 60%
“…Alves et al . () also verified that in citrus petioles, the predominant secondary cell wall deposition is the pitted type instead of the helical type predominant in grape (Fritschi et al ., ), which reinforces the hypothesis that the slower X. fastidiosa colonization in citrus compared to grape might be related to morphological differences in the xylem between these species.…”
Section: Discussionmentioning
confidence: 60%
“…Two petioles from a healthy C. arabica plant were used as control. Transmission electron micrographs of cross‐sectioned leaf petioles indicated the presence of abundant rod‐shaped bacterial cells exhibiting the characteristics of X. fastidiosa cells in the xylem vessel under different magnifications, as described previously (Alves et al ., ; Fig. ).…”
Section: Resultsmentioning
confidence: 93%
“…() and Alves et al . () suggested that the needle‐shaped crystals could respond to infections by Diaporthe citri and Xylella fastidiosa in C. unshiu and C. sinensis , respectively. The crystals, which were identified as hesperidin by Homma et al .…”
Section: Resultsmentioning
confidence: 97%